Investment yield’s affecting factors in equity crowdfunding - Astuti, Sri Wibawani Wahyuning; Sudiyono, Widhiyo; Azzahra, Laras (Journal of Multiperspectives on Accounting Literature, 2024)
Research aims: This research is a quantitative-associative study that aims to analyze the effect of a ratio of company size and NPM on investment yield registered in Santara in 2020. Design/Methodology/Approach: The population in this study is Small and Medium Enterprises (SMEs) registered in Santara and the sample of this study was 40 SMEs with sampling technique using a purposive sampling method. The statistical test in this study uses Multiple Linear Regression and the analysis tool used is SPSS Version 25. Research findings: The results of the test show that (1) company size has no effect on investment yield in SMEs (2) NPM has no effect on investment yield in SMEs. Covid-19 pandemic has made SMEs reluctant to set a Investment Yield that is too high, because it will be dangerous and lead to bankruptcy. Theoretical contribution/Originality:. This study contributes to knowledge of the Equity Crowdfunding Market, how it works. This study also contributes to prove the signal theory in Equity Crowdfunding Market. Practitioner/Policy implication: This research has implications for policy makers to consider determining investment yield based on Size and Net Profit Margin. Research limitation/Implication: The limitation of this study is the minimum of sample. Beside that, this study only focus on one Equity Crowdfunding Platform, so it cannot be generalized to other platforms considering the different policies of each equity crowdfunding platform.